Impact of Environmental Accounting Disclosure on Cost of Capital in Nigeria - Emovon, Felix Osayabor; Bosun-Fakunle, Yemisi; Okunrobo, Samuel Osarobo (The Journal of Accounting and Management, 2025)
Objectives: This study investigates the impact of environmental accounting disclosure on the cost of capital among Nigerian oil and gas companies. Specifically, the study examines whether effluents and waste disclosure, energy disclosure, enviromental laws and regulations significantly influence cost of capital. Prior Work: A review of emprical data from earlier studies reveals that prior investigations have predominantly focused on the manufacturing sector, consumer goods industries and non-financial entreprises, neglecting a concentrated examination of the oil and gas sector specifically. Further, from the analyses of previous studies, which have yielded heterogeneous outcomes; thus, suggesting the presence of incongruent findings. This study explores the impact of environmental accounting disclosure and cost of capital in Nigeria. Approach: Spanning a decade from 2014 to 2023, the study uses data derived from the annual reports and financial statements of eight publicly traded oil and gas firms listed on the Nigerian Exchange Group (NGX). Adopting an ex-post facto research design and utilizing both descriptive and inferential statistical techniques, panel-corrected standard error methods were employed for hypotheses testing. Results: Demonstrate that disclosures related to effluents and waste have a positive but statistically insignificant influence on capital costs, while adherence to environmental laws and regulations presents a negative but also statistically insignificant effect. Conversely, energy disclosure reveal a statistically significant positive impact, implying that enhanced transparency in energy reporting may be associated with higher capital costs. While effluents and waste disclosures do influence capital costs, their effect remains statistically insignificant. Implications and Value: The study advises companies to reevaluate their energy disclosure strategies, while policymakers should consider modifying regulations to alleviate potential increases in capital costs. It also enhance the extant body of knowledge by providing empricial evidence on other aspects of environmental accounting disclosure which could be relevant to the researchers.